ANALISIS SIFAT MEKANIS KOMPOSIT POLYESTER YANG DIPERKUAT SERAT KULIT DURIAN (DURIO ZIBETHINUS MURR) AKIBAT VARIASI FRAKSI VOLUME - Arthur Y. Leiwakabessy; Benjamin G. Tentua; Fany Laamena (Fakultas Teknik Universitas Pattimura, 2021)
Durian rind fiber composite as a reinforcement is one of the interesting research areas. Some of the advantages associated with using natural fibers due to reinforcement in polymers are their non-abrasive properties and low-cost consumption. Durian rind when processed further can be made into cellulose fiber which can be used as a natural filler in unsaturated polyester composites. Among various types of natural fibers, durian skin fiber is an alternative polymer composite filler. Durian skin can be obtained easily because it is a family waste that has not been used. To get a new composite material made from durian skin waste, and to help the community and government in handling durian skin waste. The purpose of this study was to determine the maximum value of the variation of the volume fraction of durian skin fiber on the impact strength and hardness strength according to the desired application. This study uses the Hand Lay Up method, in the manufacture of single fiber composites with variations in volume fraction of durian skin fiber: polyester matrix, namely, 10%: 90%, 20%: 80%, 30%: 70%, 40%: 60% and 50 %:50%. The results showed that there was an increase in the impact strength and hardness strength with the addition of the volume fraction, where the highest impact energy for the volume fraction of durian skin fiber was 50%: 50%, 0.7738 J, and the highest impact value was 0.0096725 J/mmÂ² and energy the lowest impact is 10%: 90%, 0.461 J. and the lowest impact price is 0.0057685 J/mmÂ². So it can be concluded that the impact strength and hardness of the durian skin fiber composite increased with the increase in the volume fraction of the fiber.